The Contribution of Fisheries Sector to Achieving Food Security in Algeria: An Analytical Study - Boukeltoum , Mohamed; Guedri , Salah Eddine (Finance and Business Economies Review, 2023)
Achieving food security is an important priority in public policy, as the world has witnessed a significant increase in demand for food in recent years. Like all countries in the world, Algeria seeks to obtain resources that can contribute to food security. Among these resources are fishing resources, which are one of the most important sources of food for humans due to their high nutritional and economic value. The current study intends to examine the contribution of the fisheries sector to contribute food security in Algeria by providing and ensuring the sustainability of fishing resources in order to support food security policies, through the use of mathematical equations that determine the food gap from fish consumption between 2010 and 2019 in Algeria, based on statistics from the National Statistics Office and the fish consumption rate set by the World Health Organization at 6.2 kg per person per year. The results showed that the contribution of the fisheries sector to supporting food security policies in Algeria is very limited, due to several particular biological reasons, also imports from this sector are still far from achieving global consumption rates of fishing resources.